Reklama matnining kommunikativ-pragmatik xususiyatlari - N. QANOATOVA, X. ABDULLAYEVA (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The communicative-pragmatic goal of speech communication is hidden in advertising discourse. In the discursive field, the process of any advertisement influencing the consumer is reflected.